Explaining the Body Mass Index Gaps between Turkish Immigrants and Germans in West Germany 2002-2012: A Decomposition Analysis of Socio-economic Causes - Rui Dang (Center for Economic Studies and ifo Institute (CESifo), 2015)
In this paper, we decompose body mass index (BMI) differences between Turkish immigrants and Germans in West Germany for women and men. We focus on isolating the part of BMI differences that can be explained by differences in observed socioeconomic status from the part attributable to differences in coefficients. Our results reveal that female Turkish immigrants are on average more obese than female Germans; however, there exists no significant difference in obesity among males. Our results also indicate that differences in socioeconomic status between female Turkish immigrants and Germans explain significant parts of the obesity disparities between these two groups. This paper presents research output of the Ifo Center of Excellence for Migration and Integration Research (CEMIR)
Keywords: J15; I14; C21; 330; BMI disparity; Turkish immigrants in Germany; decomposition; quantile regression